The gender effects of COVID-19 on equity analysts - LI, Frank Weikai (Institutional Knowledge at Singapore Management University, 2021)
We use the COVID-19 pandemic as a natural experiment to study the effects of childcare and household duties on sell-side analysts. The richness of this setting allows us to compare female and male analysts while requiring them to perform the same tasks. We find that female analysts' forecast accuracy declined more than male analysts, especially when schools were closed and among analysts who were more likely to have young children, inexperienced, were likely busier before the pandemic, and lived in southern states. Female analysts also reduced the timeliness of their forecasts and resorted to more heuristic forecasts. The stock market was aware of this and became less responsive to female analysts' forecasts. However, female analysts did not reduce their coverage or updating frequency relative to male analysts. We also find the above widening gender gap was temporary and became statistically insignificant by May/June 2020. Overall, our results show that the pandemic impacted female analysts more than males through the quality of their forecasts but not the quantity.